Factors Related Tax Avoidance on Food and Beverage Manufacturing Companies Listed in Indonesia Stock Exchange Period 2017-2020 - Mutmainah (HM Publisher, 2022)
Tax avoidance is an effort to reduce the burden of taxes paid but is carried out legally and ethically, and does not conflict with the applicable tax rules. This study aims to determine the factors that influence tax avoidance, with a focus on analyzing the variables of leverage, profitability, and capital intensity. The design of this research is analytic observational. The research subjects are manufacturing companies in the food and beverage sector which are listed on the Indonesia Stock Exchange in 2017-2020. There were 11 companies that meet the sample criteria. The results of the analysis show that the mean + SD on the tax avoidance variable is 0.887+1.973. The mean + SD on the leverage variable is 0.498+0.622, the profitability variable is 0.913+2.781, and the capital intensity variable is 0.729+ 0.794. In conclusion, the factors of leverage, profitability, and capital intensity have no effect on tax avoidance in food and beverage manufacturing companies on the Indonesia Stock Exchange in 2017-2020.